PENGARUH SUMBER MEDIA PELARUT NUTRISI PADA TEKNOLOGI HIDROPONIK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PAKCOY (Brassica rapa L.) - Javandira, Cokorda; Putu Lasmi Yuliyanthi Sapanca; Putu Eka Pasmidi Ariati; Yunus Wides Bani (Faculty of Agriculture and Business, Universitas Mahasaraswati Denpasar , Kec. Denpasar Utara, Kota Denpasar, Bali 80233, 2024)
Brassica rapa L or commonly called mustard pakcoy is one of the most popular types of vegetables in Indonesia, because mustard pakcoy is one of the varieties that contain various health benefits. This study aims to determine